Search for a low-mass pseudoscalar Higgs boson produced in association with a b(b)over-bar pair in pp collisions at root s=8 TeV - Khachatryan, V. (2016)
A search is reported for a light pseudoscalar Higgs boson decaying to a pair of tau leptons, produced in association with a b (b) over bar pair, in the context of two-Higgs-doublet models. The results are based on pp collision data at a centre-of-mass energy of 8 TeV collected by the CMS experiment at the LHC and corresponding to an integrated luminosity of 19.7 fb(-1). Pseudoscalar boson masses between 25 and 80 GeV are probed. No evidence for a pseudoscalar boson is found and upper limits are set on the product of cross section and branching fraction to tau pairs between 7 and 39 pb at the 95% confidence level. This excludes pseudoscalar A bosons with masses between 25 and 80 GeV, with SM-like Higgs boson negative couplings to down-type fermions, produced in association with bb pairs, in Type II, two-Higgs-doublet models. (C) 2016 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommonnorg/licensesiby/4.01).